Design and Optimization of New Two-Pole Line-Start Permanent Magnet Synchronous Motor for Pump - LIU Cheng, WANG Xiaoguang, YIN Hao, ZHANG Guoguang, XIONG Chang (Shanghai Jiaotong Daxue xuebao)
Line-start permanent magnet synchronous motor (LSPMSM) has a great application potential in the field of water pump due to its self-starting ability, high efficiency, and high power factor. In order to improve the transient performance of the motor with pump load, a new type of asynchronous starting motor rotor topology with non-uniform distribution of rotor bar is proposed. By combining the non-uniform distribution of rotor bar with the built-in permanent magnet into a multi-layer magnetic flux barrier rotor structure, the rotor salient ratio is increased, and the pull-in synchronization ability of the motor is improved. Based on the finite element method, the no-load back EMF, starting ability, pull-in synchronization ability, steady-state electromagnetic torque, demagnetization, stress field, and temperature field distribution of the traditional structure motor and the new structure motor are comprehensively compared and analyzed. The results show that compared with the traditional rotor structure, the new rotor structure effectively improves the pull-in synchronization ability, the efficiency, and the power factor of the motor under rated operating conditions. Finally, a prototype is made and an experimental platform is built to verify the correctness of the simulation results and theoretical analysis.